Cloud Computing Technologies for Privacy Data and Digital Security Authentication: A Literature Survey - Sarang, Rakesh Prasad (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a model for enabling ubiquitous convenient, where the resources of a data center are shared using virtualization technology. Cloud computing is one of the dynamic provisioning technology. Cloud computing technology can be implemented in a wide variety of architectures under different services and deployment models. Privacy to the data stored in cloud server is a major challenging operation in cloud computing. The objective of this paper is to explore different methods for efficiently growing latest digital techniques. The main aim of this paper is to design and propose strong security system to the data stored in the cloud system. This paper presents a literature review we studied the background work of carried-out by the various approaches about the uses of cloud technology. We have proposed framework and different methods which provides, identification of high protection. The literature review presents previous studies related to the objectives of the present study. Further various features that make the proposed framework more suitable for analysis and evaluation of cloud computing. The privacy cloud algorithms are categorized into subgroups according to the high level security concerns in the cloud computing